A1.1 Parent/nurse-controlled analgesia: is there a need? exploring the views of parents and nurses. (4th October 2017) - Middleton, J; Peters, J; Howard, R
Abstract : Background: Nurse-Controlled Analgesia (NCA) is a technique used for the administration of intravenous (IV) opioids for pain management in children and young people, including neonates, infants, pre-school children or those with physical or cognitive impairments with moderate to severe post-operative and non-surgical disease related pain. It has been suggested that there are potential limitations of NCA technique and some US hospitals have implemented Parent/Nurse-Controlled Analgesia (P/NCA), where in addition to the health care professional, a parent or guardian, following training is authorised to administer bolus doses. It has been suggested that the P/NCA technique has the potential benefits to parents and their children of improved pain management due to more prompt administration of boluses along with enhanced parental involvement and satisfaction. The aim of this study was to evaluate the current use of Nurse-Controlled Analgesia (NCA) in our hospital and to examine the potential need for the introduction of Parent/Nurse-Controlled Analgesia (P/NCA). Methods: The views of parents whose children had received NCA (n=30) and the nurses caring for children on NCA (n=97) were collected using questionnaires over a four week period and analysed using a combination of descriptive and inferential statistics. Results: High levels of satisfaction and good ratings for promptness of bolus administration did not provide strong evidence to demonstrate a need for P/NCA to replace current practice using NCA; however 60% of parents suggested that they would like to be trained to use P/NCA if it were available. Conclusion: P/NCA may be both appropriate and potentially beneficial in some situations however use would need to be decided based on a strict suitability and selection criteria and supported with clear protocols and educational preparation. The recommendation was that the use of P/NCA should be considered only in specific cases where there is an identifiable need.